Studi Kelayakan Gas Insulated Switchgear di PT. Paiton Operation & Maintenance Indonesia Unit 8 - Rohmanita Duanaputri; Imron Ridzki; Mohammad Iqbal Yulianto; M. Syarif Hidayatullah (Politeknik Negeri Malang, 2021)
Protection systems are a collection of components that have the same purpose to protect or secure. One of the existing protection systems in the generator is switchgear. At PT. Paiton Operation & Maintenance Indonesia Unit 8 using a switchgear insulated with SF6 gas is called gas insulated switchgear. Gas Insulated Switchgear is the newest of the Switchyard innovations. Innovations that have been developed from air isolation into gas insulation have fewer land use advantages and a better level of density. In determining the feasibility of gas insulated switchgear PT. Paiton Operation & Maintenance Indonesia performs tests consisting of insulation resistance measurements, resistance measurements, gas leakage checks, polarity checking, gas density detectors, testing duration closure and circuit breaker opening. Each test has a pre-defined value limit. Gas Insulated switchgear is said to be feasible to operate when it meets the specified value limits on each test.